Hawksbill Nesting in Hawai‘i: 30-Year Dataset Reveals Recent Positive Trend for a Small, Yet Vital Population - Alexander R. Gaos (Frontiers Media S.A., 2021)
Evaluating wildlife population trends is necessary for the development of effective management strategies, which are particularly relevant for highly threatened species. Hawksbill marine turtles (Eretmochelys imbricata) are considered endangered globally and are rare in Hawai‘i. Remnant hawksbill nesting beaches were identified in Hawai‘i in the late 1980s and the primary sites have been monitored since that time. In this study we summarize all available hawksbill nesting activity around the Hawaiian Islands between 1988 and 2018, highlighting relevant demographic and geographic data for the species. Because monitoring effort varied substantially across space and time, we implemented a predictive modeling approach that accounted for varying effort to explore potential trends in annual number of nesting females and nests over time. Field monitoring efforts documented an annual average of 14 ± 4.3 (range: 5–26) nesting females and 48 ± 19.0 (range: 12–93) nests, with a cumulative total of 178 individual nesting females and 1,280 nests recorded across all years. Nesting has been documented on four Hawaiian Islands, with the overwhelming majority of nesting females (78.4%) and nests (86.5%) recorded at four beaches along the southern coast of Hawai‘i Island. Recent monitoring (2018) at a beach on Moloka‘i Island revealed numbers similar to the most important beaches on Hawai‘i Island. Despite difficulty discerning obvious trends when looking solely at the raw tabulated numbers from field monitoring, our analysis suggests both the number of nesting females and nests have been positively trending since 2006, and this is supported by a higher percentage (57.1% of annual cohorts) of neophyte (vs. remigrant) nesters over the second half of the monitoring timeframe. The masking of obvious trends in the tabulated numbers is likely due to decreased overall monitoring effort as a result of reduced funding in recent years, coupled with a shift in focal monitoring effort from the historical primary nesting site of Kamehame, to the more recently established nesting site of Pōhue. Although the positive trend is encouraging, our findings highlight the precarious state of hawksbills in Hawai‘i and the need to enhance monitoring across all sites to support more robust population assessments and management decision making.